Morfologia rodzin polskich w świetle danych z narodowego spisu powszechnego z dnia 7 grudnia 1978 r. - Romaniuk, Kazimierz (Wydział Prawa i Administracji UAM, 1981)
On the ground of initial results of the National Census recently carried out an attempt has been undertaken to present the situation and structure of households and families in Poland. On the day of the Census Poland numbered 35,061,000 people, 10,048,000 households, and 9,435,000 families. One-family households prevailed (77,8%), especially in the country, where they amounted to 81,4% of the total number of households. The share of two-family households is insignificant not only in towns, where they amounted to 3,8%, but also in the country (6.2%). The share of three-family households, or even larger, is insignificant (0,1%). It delivers a picture of decay of multi-generation families in Poland, which existed in the past. A predominating place is occupied by a model of family consisting of both parents and children (63,6%). Families consisting of a mother all alone and her children amount to 11,8%, and of a father and children only to 1,5% of the total number of families. In the subsequent part of the article the problem of the number of children in families has been considered, as well as the problem of so called economic number of children. It results from it, that country families pay substantially higher economic efforts in favour of the process of generation replaceability than urban families.
Families in the Light of Results of the National Census of December the 7th, 1978